AAGBS Annual Report 2021: at a glance - UiTM, AAGBS (Arshad Ayub Graduate Business School (AAGBS), 2021)
AAGBS is the most prominent graduate school in UiTM with the largest enrolment. Our signature Master in Business Administration (MBA) program is flexible with full-time and part-time mode. It provides an understanding of strategic business models, contemporary issues and appreciation of responsible and sustainable leadership values that are very much demand in today’s market. Other Programs being offered include Master of Islamic Banking and Finance (MIBF), Doctor Of Business Administration (DBA) and Doctor of Philosophy AAGBS commemorates close collaboration with key industry players and leverage on strategic international partners. Our postgraduate programs are highly regarded by the local business community and across borders. Students have the opportunity to participate in international exchange programs, obtain a dual-master degree, or be co-supervised by both local and international university partners. AAGBS is proud of our highly qualified academia that is expert in various fields with vast experience. (Business Management) (PhD).